Pengolahan Limbah Cair Tekstil Menggunakan Proses Elektrokoagulasi Dengan Sel Al — Al - Bambang Hari Prabowo (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2012)
Wastewater and its problems will emerge where human being have activity, thrown volume household wastewater can reach more than 60%. Industrial wastewater around 30-40%, but is always assumption contributor of biggest environ-mental pollution. Till now many industry not yet doing treating of wastewater to lessen burden of pollutant yielded before thrown to water body. Reason of the core important is operating expenses which is high enough. Pre-treatment like aeration in pond or basin, adding chemicals to precipitated pollutant especially heavy metal which generate color and dangerous ought to earn to be done by every industry. Because continuity produce and the long time pre-treatment of wastewater causing all industrialist unwilling to operate pre-treatment is mentioned. Electrocoagulation is not a new technology, but in Indonesia not yet applied in social activities in its applying. This process modestly and easy to applied good ability in coagulation of pollutant, for organic and inorganic materials. In this research using plate ofaluminium and iron, and also combination from both.